Monopol producentów jako źródło nieformalnych procesów zarządzania - Trojanek, Jacek (Wydział Prawa i Administracji UAM, 1987)
In the present article, the author points out to the fact that the producers who are monopolists on a socialist market try to take advantage of their market power by carring out monopolistic policies aimed at becoming independent of the environment and subordinating it to their particular interests. Subordinating the environment, the monopolist determines his own authoritarian rules of cooperation with other units, contrary to the law in force, moral norms and the rules of economic play determined by the economic center. In effect, the latter is often vested with formal authority only, whereas the monopolists perform the role of informal, though influencial, managing units. Besides, the producers-monopolists strive also to become independent of the administrative and economic center or even try to impose their will on administrative and economic authorities in order to secure for themselves profits, preferences and protectionism. According to the author, compelling the superior agencies to take decisions favourable to monopolists is tantamount to their performing — to some extent — the managing functions also with respect to the administrative and economic center. The usurpation by the producers monopolizing the market of the right to administer other units is the cause of divided authority and undesired conflicts of roles in the economy.
The producers' monopoly as a source of informal management processes